Deep-seated large-scale toppling failure in metamorphic rocks：a case study of the Erguxi slope in southwest China - Liu, Ming; Liu, Fang-zhou; Huang, Run-qiu; Pei, Xiang-jun (Journal of mountain science, 2016)
Deep-seated large-scale toppling failure presents unique challenges in the study of natural slope deformation process in mountainous regions.An active deep-seated toppling process was identified in the Erguxi slope located in southwest China,which affected a large area and damaged critical transportation infrastructure with the volume of the deforming rock mass exceeding 24×10~6 m~3.It poses significant risks to the downstream Shiziping Hydropower Station by damming the Zagunao River.Field investigation and monitoring results indicate that the deformation of the Erguxi slope is in the advanced stage of deep-seated toppling process,with the formation of a disturbed belt but no identifiable master failure surface.It was postulated that the alternating tensile and shear strength associated with the hard/soft laminated rock strata of metasandstone and phyllite layers preclude the development of either a tensile or shear failure surface,which resulted in the continuous deformation and displacement without a catastrophic mass movement.The slope movement is in close association with the unfavorable geological conditions of the study area in addition to the construction of transportation infrastructure and the increase of the reservoir level.On the basis of the mechanism and intensity of the ongoing toppling deformation,a qualitative grading system was proposed to describe the toppling process and toevaluate the slope stability.This paper summarized the field observation and monitoring data on the toppling deformation for better characterizing its effect on the stability of the Erguxi slope.The qualitative grading system intends to provide a basis for quantitative study of large-scale deep-seated toppling process in metamorphic rocks.